Deterritorialization and citizenship of the Guaymí. - Solano-Acuña, Ana Sofía (Revista Geográfica de América Central., 2018)
This is an experience where geography, anthropology and history come together in order to reveal the insurgent and anti-colonial identity of western Panama, particularly of the Guaymí people. After national history it is necessary to discover regional history and ethnic history in particular, both absorbed by homogenizing and totalizing discourses where the polyphony of dissenting voices has been erased. From the late nineteenth and early twentieth centuries the idea of ​​"empty space" coexisted and competed with that of "wild space", which is possible to trace in the press, official documentation and writings of intellectuals. In this issue I want to take a tour of the strategies (political, economic and ideological) of the State and the elites to tear down the ethnoterritory and administer the indigenous population and its assets in the framework of a National State in consolidation and an exclusive national identity in the process of construction.